UAV/drone zoning in urban planning: review on legals and privacy - Hj. Mohd. Noor, Norzailawati; Mastor, Intan Siti Zulaikha; Abdullah, Alias (2017)
The use of drones or Unmanned Aerial Vehicles (UAVs) in commercial applications has the potential to dramatically alter several industries, and, in the process, change our attitudes and behaviors regarding their impact on our daily life. This paper is attempts to review a legal and privacy in urban planning context regards to the use of Unmanned aerial vehicle (UAV)/drones provided by interna-tional and local approached. It is including studied an impacts of these existing policies to the usage of drones in the urban planning context. The review consists of comparing an existing law, prohibition, restriction and guideline in drone op-eration to preserve safety and security of the people, property and environment. Few items need to be measure in designing the zones such as safety, security and privacy based on the technical and airspace aspects. Thus, by evaluating existing laws and regulations practiced in countries around the world, it will assist in de-signing drone zoning especially in Malaysia which able to manage urban planning practices and to regulate a general guidelines of zoning drone based on banned/prohibited, restricted and allowed/controlled zones within the urban con-text and ensuring the livability and resiliency of cities.